The La Coulee Formation, a new post-Acadian continental clastic unit bearing groundwater calcretes, Gaspe Peninsula, Quebec - Jutras, Pierre; Prichonnet, Gilbert; von Bitter, Peter (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1999)
A I km2 erosional remnant of the La Coulee Formation, a previously unrecognized stratigraphic unit, has been studied in the Perce area of the Gaspd Peninsula. It unconformably overlies folded Cambrian to Devonian rocks and is unconformably overlain by the mid-Carboniferous Bonaventure Fonnation. The erosional remnant includes the lowest 60 m of this newly identified formation of unknown thickness. Original sedimentary fades are limited to 50 m of breccia debris flows passing stratigraphically upward into 10m of conglomeratic debris flows. Groundwater calcrete formation has partially or completely transformed the lowest 30 m of the sequence. The depositional environment is interpreted as being related to a proximal continental alluvial fan. The nearby presence of a saline body of water is inferred to account for thick and massive groundwater calcrete formation and water-saturated debris flows in a relatively arid climatic context Most of the formation was eroded prior to deposition of the Bonaventure Formation. However, the basal groundwater calcretes were more widely preserved. They underlie the Bonaventure Formation in most of the Perce1 area and in the Saint-Elzear area, close to a hundred kilometres to the southwest. Post-sedimentary faulting has affected both the La Coulee and Bonaventure formations.